Shifting Paradigms of Research in English Studies in India - Asaduddin, Mohd (KnE Social Sciences, 2019)
English Studies in India has undergone significant changes, leading to a shift in research paradigms. Right through the British colonial period of nearly two hundred years English literature and language were used as important instruments of political domination and acculturation. Even after the British colonialism ended the dominance of English continued in all spheres of life. English has become the language of the privileged class and studying English literature a symbol of prestige. However, in its quest for relevance, English Studies had to incorporate new areas of knowledge under its purview. Literary theory made a big splash in English Studies and changed the way of approaching and assessing literature. English Studies also saw rigorous debates about the relationship between English Literature and ELT and different approaches in their pedagogy. Then, postcolonial literature and theory made its impact felt in the field. Two other domains that have enriched the field of English Studies are Comparative literature and Translation Studies. English writings emanating from India grew in plenitude and self-assurance and the language itself underwent substantial change to acquire its distinct Indian characteristics. Literatures produced in 24 Indian languages are being copiously translated into English and researches in English studies are happening at this contact zone of creative literature in English and literature available in English translation. Keywords: English Studies, Literary Theory, ELT, Comparative literature, Translation Studies, Literary History